Residential Parking Permits and Parking Supply - Jos van Ommeren; Jesper de Groote; Giuliano Mingardo (Tinbergen Institute, 2013)
We estimate welfare losses of policies that provide on-street parking permits to residents almost free of charge in shopping districts. Our empirical results indicate that parking supply is far from perfectly price elastic, implying that there are substantial welfare losses related to under-priced parking permits. Our results suggest that the provision of residential parking permits in shopping districts induces a yearly deadweight loss of at least euro 500 per permit, which is about 30% of the supply cost of a parking place in shopping districts.
urn:NBN:nl:ui:15-1765/39844
Keywords: R41; R48; 330; parking supply; residential parking permit; deadweight loss; Ruhender Verkehr; Angebot; Preiselastizität; Einkaufszentrum; Wohlfahrtsanalyse